Interrupting Voice in Cyber Media: Standing and Rationales of Indonesian Ulema Council (MUI) of West Sumatera in Rejecting Religious Moderation Campaign - Febri Nanda, Hilman; Naupal (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This article discusses legal position of West Sumatra’s Indonesian Ulema Council in responding to religious moderation campaign offered by Government. On many occasions, West Sumatra’s Ulema Council has shown their rejection and objection to various religious concepts popularized by State Institution. This rejection was not only given to the people of West Sumatra, but also propagated through other cyber channels, such as social media and their official online platforms. This study is based on library research and field data. Using Jürgen Habermas' public sphere theory, this article explains how such their standings might be viewed as dialogical challenges to keep the public sphere remains an enabling venue for religious dialogue. The arguments they present through various cybermedia channels have an intrinsic correlation to the conceptions they criticize. Through cyberspace, responses, confirmations, and arguments between communication subjects can also be seen, which keeps the religious discourse being discussed relevant. By not confirming which standing is the strongest and most universal in religious moderation, this article demonstrates that the robustness and universality of a religious campaign require public sphere, such as this cyberspace, and those who use that space as a means of rational consideration can then be accepted and evaluated by the public at large.